A practical multigram-scale method for the green synthesis of 5-substituted-1H-tetrazoles in deep eutectic solvent. Issue 5 (31st January 2019) - Xiong, Xingquan; Yi, Chao; Liao, Xu; Lai, Shilin
Graphical abstract: Highlights: Practical one-pot reaction for preparation of 5-substituted-1 H -tetrazoles. Without using high boiling point or volatile organic solvents in the reaction. Easy reaction set-up and multigram scale. Abstract: A series of 5-substituted-1 H -tetrazoles have been efficiently synthesized in moderate to excellent yields (68–90%) under mild reaction conditions by combining aryl aldehydes, hydroxylamine hydrochloride with sodium azide in the presence of catalytic amount of Cu(OAc)2 in deep eutectic solvent (DES). The new synthetic method has many advantages, such as high conversion, green reaction medium, easy work-up, low cost, and environment friendly.